The effects of microstructure and growth rate on microhardness, tensile strength, and electrical resistivity for directionally solidified Al-Ni-Fe alloys - Engin, Sevda; Buyuk, Ugur; Marasli, Necmettin (ELSEVIER SCIENCE SA, 2016)
Directional solidification of eutectic alloys attracts considerable attention because of microhardness, tensile strength, and electrical resistivity influenced by eutectic structures. In this research, we examined processing of Al-Ni-Fe (Al-6.5wt.%Ni-1.5wt.%Fe) eutectic by directional solidification. The alloy was prepared by vacuum furnace and directionally solidified in Bridgman-type equipment. During the directional solidification process, the growth rates utilized varied from 8.25 mu m/s to 164.80 mu m/s. The Al -Ni-Fe system showed a eutectic transformation, which resulted in the matrix Al, rod Al3Ni, and plates Al9NiFe phases. The eutectic spacing between (lambda Al3Ni - lambda Al3Ni, lambda Al9NiFe - lambda Al9NiFe) was measured. Additionally, the microhardness, tensile strength, and electrical resistivity of the alloy were determined using directionally solidified samples. The effects of growth rates on microhardness, tensile strength, and electrical resistivity for directionally solidified Al-Ni-Fe eutectic alloy were investigated, and the relationships between them were experimentally obtained. It was found that the microhardness, tensile strength, and electrical resistivity were affected by both eutectic spacing and the solidification parameter. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Directional solidification; Aluminum alloy; Microstructure; Electrical properties; Tensile test; Hardness test; MECHANICAL-PROPERTIES; UNIDIRECTIONAL SOLIDIFICATION; DENDRITIC MICROSTRUCTURE; PARAMETERS; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering